Pre-service instruction training for tradesmen employed to teach evening trade extension classes - Holmes, Forrest A., author; Hinderman, Roy Aaron, 1900-, advisor; Marshall, Thomas O., committee member; Henry, George F., committee member; Britton, Russell K., committee member (Colorado State University. Libraries, 1944)
To view the abstract, please see the full text of the document.
Keywords: Teachers -- Training of; Industrial arts -- Study and teaching; Evening and continuation schools